Effects of Peripheral Administration of Kisspeptin on Pubertal Maturation and Serum Leptin Levels in Female Rats - Alcin, Ergul; Ozcan, Mete; Ayar, Ahmet; Yilmaz, Bayram; Turkoz, Yusuf; Kelestimur, Haluk (Ortadogu Ad Pres & Publ Co, 2011)
Objective: The aim of this study was to investigate the effects of exogenous kisspeptin on pubertal maturation in immature female rats. Material and Methods: Wistar female rats were weaned when they were 21 days old. The rats were divided into two groups. Controls (n=10) received saline only (1 ml/kg). Experimental rats (n=9) were intraperitoneally injected with daily 100 nmol kisspeptin-10 between 09.00h-10.00h a.m. starting from the day 26. Body weight and food intake were daily determined, and vaginal opening (VO) was daily monitored starting from day 26. The animals were decapitated when the first diestrus was determined by vaginal smears. Upon decapitation, serum was separated and stored at -20 degrees C until measurement of leptin, luteinizing hormone (LH) and estradiol. Uterus and ovaries were dissected out and weighed. Results: Intraperitoneal injection of 100 nmol kisspeptin-10 did not change median VO ages. There were no differences in food intake, and percentages of body weight change, between control and kisspeptin groups during the experimental period. Kisspeptin administration elicited significant (P<0.01) increases in uterus weight over control values. Serum leptin levels were significantly lower (P<0.05) in kisspeptin-treated group compared to vehicle group. Kisspeptin administration increased (P<0.05) serum LH and estradiol levels. Conclusion: Chronic peripheral administration of kisspeptin-10 does not advance puberty onset as estimated from the date of vaginal opening, but potentiates other conventional indices of maturation of reproductive axis such as elevated uterine weight and increased serum levels of LH and estradiol.
Dişi ratlarda pubertal O1gunlaşma ve serum leptin seviyeleri üzerine periferik kisspeptin uygulanmasimn etkileri
Keywords: Puberty; kisspeptin-10; leptin